Bibliographic data retrieval using query optimization techniques in Mongodb - Ramasamy, Chitra; Zolkepli, Maslina (Institute of Advanced Scientific Research, 2020)
The rise of unstructured, semi structured and structured data making the data exploration task more and more challenging. The technologies are evolving especially the databases to tackle the rapidly growing data to get a meaningful insight. NoSQL (Not Only SQL) comes into picture to manage the distinguished characteristics of big data. The publications recorded in Digital Bibliography and Library Project (DBLP) also increasing steadily from 1936 until 2019 reaching the number 4,886,660 publications. A proper storage and retrieval technique are needed to get these data to be available for view with faster response time for any young researchers comes into the computer science field. This paper will be exploring the query optimization techniques in MongoDB using bibliographic data.